Pengaruh Model Pendampingan Ibu pada Program Posyandu terhadap Perubahan Status kebersihan Gigi dan Mulut Balita - Yenny Lisbeth Siahaan; Supriyana Supriyana; Irma Siregar (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
The objective of this study is to analyze the effect of the assistance model in mother to improve oral hygiene and mouth of toddlers under the age of 2-5 years. Methods: The study design was a quasi-experiment in the form of non-randomized pre-post test control group. The intervention group received assistance model by cadres companion and dental health professionals (researchers) and the control group received counseling by dental nursing workers in posyandu. Number of subjects 30 toddlers. Variables observed included changes in knowledge, attitudes, skills and levels of maternal oral hygiene toddlers (PHP-M scores). Data analysis was performed using bivariate different test. Results: After 3 weeks of intervention occurs very significant increase in the mean knowledge score of the mothers (0.05), the level of oral hygiene toddlers (PHP-M) (p0.005), then the skills and attitudes of each mother's mean score (p 0.005). Where as in the control group there was no difference in PHP-M toddlers mean PHP-M scores (p 0.005). Conclusion: Extension efektjf assistance model more than the extension in posyandu in improving the oral hygiene of toodlers.